2020
DOI: 10.31014/aior.1992.03.02.226
|View full text |Cite
|
Sign up to set email alerts
|

https://www.asianinstituteofresearch.org/JEBarchives/Does-Bangladesh-Need-to-be-Established-Derivatives-Markets%3F

Abstract: Derivatives are very cardinal agreement, not just for the purpose of investors but for the overall economies. They excellently affect the general execution of a nation's economy and along these lines the global economy. The world derivative markets are gigantic and it has developed widely in the last decades in both developed economy and rising economy. Derivative markets protect bonds, currency, equity, and short-term interest rate assets from various risks. Bangladesh is a developing country it has an emergi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 2 publications
1
1
0
Order By: Relevance
“…More specifically, the framework argues that the three proposed drivers or stimuli of social media advertising (i.e., entertainment, interaction, and e-WOM) interact to both brand image and consumers' intention to purchase. This assertion is supported by similar studies in the field (Seo and Park, 2018;Işık et al, 2024a;Islam et al, 2022;Işık et al, 2024b;Dehghani et al, 2015;Islam et al, 2024;Bilgin, 2018;Algharabat, 2017;Rana et al, 2023;Islam et al, 2020;Godey et al, 2016;Islam et al, 2021). Within this context, Seo and Park (2018) and Bilgin (2018) found that entertainment and interaction significantly influence the brand image of products in social media advertising, and e-WOM also exerts a noteworthy impact on these components (Godey et al, 2016).…”
Section: Theoretical Background and Hypotheses Developmentsupporting
confidence: 55%
“…More specifically, the framework argues that the three proposed drivers or stimuli of social media advertising (i.e., entertainment, interaction, and e-WOM) interact to both brand image and consumers' intention to purchase. This assertion is supported by similar studies in the field (Seo and Park, 2018;Işık et al, 2024a;Islam et al, 2022;Işık et al, 2024b;Dehghani et al, 2015;Islam et al, 2024;Bilgin, 2018;Algharabat, 2017;Rana et al, 2023;Islam et al, 2020;Godey et al, 2016;Islam et al, 2021). Within this context, Seo and Park (2018) and Bilgin (2018) found that entertainment and interaction significantly influence the brand image of products in social media advertising, and e-WOM also exerts a noteworthy impact on these components (Godey et al, 2016).…”
Section: Theoretical Background and Hypotheses Developmentsupporting
confidence: 55%
“…A variety of research on economic elements, some of them including macroeconomic variables, influence bank financial performance (Asif et al, 2023;Brahmaiah, 2018;Kirimi et al, 2020;Petria et al, 2015;Işık et al, 2021Işık et al, , 2024aIşık et al, , 2024bIşık et al, , 2024cIşık et al, , 2024d2024fIslam et al, 2024Mamun et al, 2022;Islam et al, 2020;Islam et al, 2022;Islam et al, 2023a;Islam et al, 2023b;Rana et al, 2023;Işık et al, 2024c;Işık et al, 2024dHasan et al, 2019Rahman, 2019). Inflation, gross domestic product (GDP), national income, per capita income, exchange rates, interest rates, unemployment levels, and financial crises are all macroeconomic factors that affect banks performance (Bhattarai, 2017;Cetin et al, 2023;Neupane, 2020;Ozatac et al, 2018;Saeed, 2014;Simiyu and Ngile, 2015).…”
Section: Literature Reviewmentioning
confidence: 99%